Marketing Channel Analysis, Marketing Margins, and Farmer's Share Cinnamon Commodity in Sungai Penuh City, Jambi Province, Indonesia - Chatra, Afdhal; Rosi, Adek Irma (Agro Bali : Agricultural Journal, 2023)
The cinnamon commodity is quite significant in the economy of Sungai Penuh City, but farmers have not felt its role in improving welfare. The fundamental problems faced by cinnamon farmers in Sungai Penuh City are the weak bargaining position of farmers in the pricing process due to lack of access to price information, the attachment of farmers to collecting traders, and the limited ability of farmers to develop processed cinnamon products allegedly resulting in farmers only getting a small profit from sales. Traders, collectors, and exporters process more to meet domestic and foreign market demand. For this reason, an analysis of the existing condition of marketing margins and farmers' share of cinnamon commodities in Sungai Penuh City is needed. The purpose of this study is to analyze cinnamon marketing margins between farmers, collecting traders and exporters in each marketing channel in Sungai Penuh City, analyze the amount of farmers share obtained by farmers in each cinnamon marketing channel in Sungai Penuh City, and analyze cinnamon marketing functions in the form of physical functions, exchange functions and facility functions between farmers, Collecting traders and exporters in Sungai Penuh City. To answer the study's objectives, the author uses marketing margin analysis methods, profit margin analysis, farmer's share analysis, and marketing function approaches in physical, exchange, and facility functions. This research method uses a qualitative descriptive approach, and the informants in this study are determined by purposive sampling. The results showed that as many as 60 percent of cinnamon farmers in Sungai Penuh City chose and 40 percent chose the two-actor marketing channel. In contrast, the cinnamon marketing channel involving three marketing actors showed that the marketing system was inefficient. In contrast, the cinnamon marketing channel involving two marketing actors showed that the cinnamon marketing system in Sungai Penuh City was efficient.